2005
DOI: 10.1063/1.2136424
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of AlN∕AlGaN superlattice grown by pulsed atomic-layer epitaxy for dislocation filtering

Abstract: We report the detailed structure analysis of our AlN∕AlGaN superlattice (SL) grown by pulsed atomic-layer epitaxy (PALE) for dislocation filtering. Due to the nature of PALE, the AlGaN well material itself in the SL was found to be composed actually of an AlxGa1−xN∕AlyGa1−yN short-period superlattice (SPSL), with the periodicity of 15.5Å (≈6 monolayer), determined consistently from high-resolution x-ray diffraction and high-resolution transmission electron microscopy measurements. The SPSL nature of the AlGaN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 14 publications
3
34
0
Order By: Relevance
“…Therefore, the partially relaxed SLs effectively assist in decreasing the edge TDs extending into upper Al-rich AlGaN. In comparison with the results reported by others [14], where fully strained SLs effectively reduce screw TDs but do nothing with the edge ones, it suggests that SLs' strain extent has a close relation with reducing screw or edge TDs. In our case, the function of SLs buffer on improving the crystalline quality of Al-rich AlGaN includes two aspects.…”
Section: Sapphiresupporting
confidence: 48%
See 3 more Smart Citations
“…Therefore, the partially relaxed SLs effectively assist in decreasing the edge TDs extending into upper Al-rich AlGaN. In comparison with the results reported by others [14], where fully strained SLs effectively reduce screw TDs but do nothing with the edge ones, it suggests that SLs' strain extent has a close relation with reducing screw or edge TDs. In our case, the function of SLs buffer on improving the crystalline quality of Al-rich AlGaN includes two aspects.…”
Section: Sapphiresupporting
confidence: 48%
“…Taking the (1 1 2 4) RSM as an example, the tilt broadens the RLPs along the normal to [11][12][13][14][15][16][17][18][19][20][21][22][23][24] direction, whereas the lateral coherence length broadens along the [11][12][13][14][15][16][17][18][19][20] lateral direction [24]. Thus, both broadening extents of Al 0.69 Ga 0.31 N can be estimated from its (1 1 2 4) RSM in Fig.…”
Section: Sapphirementioning
confidence: 97%
See 2 more Smart Citations
“…Substantial research [17][18][19] has shown that the development of strained-layer SLs makes it possible to grow epitaxial layers of high quality on lattice-mismatched substrates, especially for III-V materials. The strained layers serve as a series of barriers that tend to bend any misfit dislocations into the growth plane, thus preventing the propagation of dislocations into the next layer.…”
Section: Article In Pressmentioning
confidence: 99%